Effectiveness of Simulation-Based Serious Games on Numeracy Problem Solving Abilities in Elementary Schools - Masruroh, Aimatul; Crismono, Prima Cristi; Yanuardianto, Elga (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to determine the effectiveness of simulation-based serious games on the numeracy problem solving abilities of fifth grade elementary school students. The research method used was quasi-experimental pretest-posttest non-equivalent control group design . The research subjects consisted of 38 fifth grade elementary school students who were divided into two groups, namely experimental (19 students) and control (19 students). Data collection techniques use tests and observations. Data were analyzed using the IBM SPSS Statistics Version 29 application. Data validity tests included normality and homogeneity tests. The results of the research showed that the mean gain score for experimental students was 40.52 and the control group was 28.94. In the Shapiro-Wilk column The gain score in the experimental group had a sig value of 0.638 and the gain score in the control group had a sig value of 0.642. The hypothesis results obtained a sig value of 0.037, which means it is smaller than 0.05, so it can be concluded that there is a difference in the average between students in the experimental group and the control group, so that there is effectiveness in learning using simulation-based serious games in solving numeracy problems, understanding numeracy questions. , as well as performing mathematical operations